PEMANFAATAN HIJAUAN PAKAN TERNAK Brachiaria Ruziziensis DAN Stylosanthes Guianenis MENDUKUNG USAHA TERNAK KAMBING DI KABUPATEN ASAHAN - Rusdiana, S.; Hutasoit, Rijanto (Universitas Sebelas Maret, 2014)
System maintenance goats in Indonesia, especially in the District High King of the North Sumatra regency shavings Proopinsi done the traditional way, the availability of quality feed is one of the limiting factors to determine the number of livestock kept by farmers. The purpose of this paper is to investigate the possibilities among supplementary feeding is applied by farmers feed ingredients are easily available at affordable prices, livestock forage planted palm perkebunana dilahan the age of 5 years with extensive 3 ha forage crops forage Brachiaria and Stylosanthes ruziziensis Guianeniserta, as well as waste agriculture, which can increase the rate of goats nuts. Livestock production performance shows R1, R2 and R3 highly significant (P <0.01) higher than R3, whereas to measure the growth rate of goats nuts (R1) which is the regression coefficient Yk = 14:33 +2.02 X (R2) which is the regression coefficient Yk = 14.34 +1.75 x, and (R3) which regress coefficient Yp = 14.34 + 1.58 y obtained regression equation with the same value of R2= 0.99, not only petambahan weight are visible on the nut goats in ruziziensis give forage Brachiaria and Stylosanthes guianenis but goats seem nuts over fluffy, slippery, sparkling eyes, smooth and healthy. Gains derived by farmers around R1 Rp.1.058.602/bulan B/C 1.2, R2 around Rp.984.145/bulan B/C 1.2 due to variable expenses and the cost of production, while approximately R3 Rp.666.268/bulan B/C 1.1 expenditure concentrated on variable costs, labor costs and the purchase of seeds.